2019
DOI: 10.1111/conl.12674
|View full text |Cite
|
Sign up to set email alerts
|

Moderately common plants show highest relative losses

Abstract: Nature conservation efforts often focus on rare species. Common and moderately common species, however, receive much less attention. Our analysis of occupancy change of flora using a grid survey in 1980 and a habitat mapping survey in 2000 in Northeast Germany revealed significant losses for most of the 355 modeled plant species. Highest losses were recorded for moderately common species. Plant species occurring in 20–40% of grid cells declined on average by 50% in 20 years, although there were some methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…Such common specialist species are of concern because common species are often overlooked in favor of the many threatened and endangered species in Hawai'i. Even globally, common species are often overlooked, even though systemic declines associated with common species are increasingly recognized in a variety of taxa and the loss of naturally occurring common species is bound to be devastating to ecosystem structure, function, and services [107,108]. Common species on the specialist end of the continuum should be targeted for additional climate change mitigation research (e.g., physiological sensitivity analysis) to support natural area managers in the struggle to preserve and conserve biological diversity in the face of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Such common specialist species are of concern because common species are often overlooked in favor of the many threatened and endangered species in Hawai'i. Even globally, common species are often overlooked, even though systemic declines associated with common species are increasingly recognized in a variety of taxa and the loss of naturally occurring common species is bound to be devastating to ecosystem structure, function, and services [107,108]. Common species on the specialist end of the continuum should be targeted for additional climate change mitigation research (e.g., physiological sensitivity analysis) to support natural area managers in the struggle to preserve and conserve biological diversity in the face of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Some can become rare rapidly, for example the near‐total loss of once‐dominant American chestnut ( Castanea dentata ) from eastern North American forests in the early 20th century caused by the non‐native pathogen Cryphonectria parasitica (Paillet, 2002). Others show gradual, but significant declines, for example 19 abundant North American land bird species each experienced population reductions of >50 million birds over 48 years (Rosenberg et al., 2019), and common plants showed the greatest declines in occurrence over 20 years in Germany (Jansen, Bonn, Bowler, Bruelheide, & Eichenberg, 2020). Repeated national sampling of common species will provide early warning signals to prompt action (Schmeller et al., 2018; Wintle, Runge, & Bekessy, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Like in the present study, a study in north-east Germany reported that approx. 60% of the 355 studied species were declining and that moderately common species declined strongest (Jansen et al, 2020). Similarly, in north-west Germany Bruelheide et al (2020) reported significant declines for a large number of plant species, mainly herbs.…”
Section: Discussionmentioning
confidence: 99%
“…2009), regional and trans-regional scales (e.g. Bruelheide et al, 2020; Jansen et al, 2020; Finderup Nielsen et al, 2019; Jandt et al, 2011; Staude et al, 2020) and at small-scales, e.g. on the plot-level (e.g.…”
Section: Introductionmentioning
confidence: 99%